Recent Publications (Quarterly Journal of Economics, 1935)
Recent Publications The Quarterly Journal of Economics, Volume 49, Issue 4, August 1935, Pages 725–730, https://doi.org/10.1093/qje/49.4.725 Published: 01 August 1935